Kombinasi Senam Lansia dan Obat Hipertensi Berpengaruh terhadap Tekanan Darah Lansia Penderita Hipertensi - Sangadah, Arum Setiani; Mustajab, Abdullah Azam; Mulyani, Sri (Fakultas Ilmu Kesehatan, 2024)
Hypertension management can be done pharmacologically or by administering drugs and non-pharmacologically, one of which is elderly gymnastics. Hypertension if not given proper management can lead to heart disease, stroke and kidney failure. The purpose of this study was to determine the effect of a combination of elderly gymnastics and antihypertensive drugs on blood pressure in elderly people with hypertension. This research method uses a quasi-experimental design with a pre-post test nonequivalent control group design approach. The sample of this study was 39 respondents with a total sampling technique, the intervention group consisted of 20 respondents and the control group consisted of 19 respondents. The hypothesis test of this study used the T-test because the data was normally distributed with a p-value> 0.05. The results of this study obtained a significance value of systolic and diastolic pressure in the intervention group p-value = 0.000, while in the control group the significance value of systolic blood pressure p-value = 0.000 and diastolic pressure p-value = 0.048. So it can be stated that the decrease in blood pressure in the intervention group was more optimal than in the control group. Conclusion: There is an effect of giving a combination of elderly exercise and antihypertensive drugs on the blood pressure of elderly people with hypertension